A Case of Thyrotoxic Periodic Paralysis and Graves’ Ophthalmopathy Patient in Coincidence with Chronic Hepatitis B Infection - Ginting, Herry Krisnata; Adi, Soebagijo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Graves' disease is an autoimmune thyroid disease with several characteristic symptoms and signs. Graves' ophthalmopathy, an inflammatory disease in the orbital area, is the main extrathyroid manifestation of Graves' disease. About 5% of Graves' ophthalmopathy patients have moderate to severe severity requiring high doses of systemic corticosteroid therapy. Graves' disease also has few complications, one of which is thyrotoxic periodic paralytic characterized by hypokalemia and muscle paralysis. Chronic hepatitis B virus infection has the potential to be co-incidence with other diseases (eg Graves ophthalmopathy). The need of high dose of corticosteroid therapy in treating Graves’ ophthalmopathy is a risk of reactivation in hepatitis B infection patient. This paper presented a Graves' disease patient complicated with Graves’ ophthalmopathy who developed limb muscle weakness. Patient will receive high doses of corticosteroids and prophylactic lamivudine therapy to prevent hepatitis B virus reactivation.